Fabrication and characterizations of hybrid membrane containing tannin-modified metal-organic framework for water treatment - Johari, N. A. (2021)
In the past decade, many researchers have focused on incorporating metal-organic frameworks (MOFs) as filler for hybrid membrane fabrication, predominantly due to their excellent polymer affinity, huge porosity, and tunable pore size. The hybrid membrane can significantly improve overall membrane properties. However, MOF/polymer membranes usually suffer low flux due to the hydrophobic nature of MOF's organic linker. Herein, this study modified MIL-100 an iron-based MOF with tannic acid to improve its hydrophilicity and subsequently hybrid membrane was fabricated using the phase inversion technique. Vast hydroxyl group from tannic acid plays an essential role in improving the hydrophilicity of MOF. Subsequently, improved the hydrophilicity of the prepared membrane. The Tannin-MOF/PES membrane experienced a high pure water flux of 357.9 L/m2h, which is 1.9 times higher than the unmodified PES membrane.